1975
DOI: 10.1152/jappl.1975.38.5.786
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory effects of rapid saline infusion in normal man

Abstract: We have studied the cardiorespiratory effects of the rapid infusion (100 ml/min) of 2 liters of saline in four normal seated subjects. Cardiac output and pulmonary arterial pressure increased, while vital capacity (VC) and total lung capacity (TLC) decreased. There was an increase in closing volume (CV) without any detectable change in lung compliance or flow-volume characteristics. There was an increase in Pao2 during infusion period which can be related to better matching of ventilation to perfusion and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 0 publications
8
40
1
Order By: Relevance
“…Rapid intravenous infusion of an isosmotic solution, such as saline 0.9%, is expected to be followed by fluid leakage from both pulmonary and bronchial vessels (7,10,13,16,22,(30)(31)(32)(33). The ensuing events include filling of the spaces around the alveoli and the complex vascular network accompanying the airways (29), likely promoted by negative interstitial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid intravenous infusion of an isosmotic solution, such as saline 0.9%, is expected to be followed by fluid leakage from both pulmonary and bronchial vessels (7,10,13,16,22,(30)(31)(32)(33). The ensuing events include filling of the spaces around the alveoli and the complex vascular network accompanying the airways (29), likely promoted by negative interstitial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence in animals demonstrates that airway wall edema resulting from vascular engorgement increases peripheral airway resistance (13,30) and potentiates the response to chemical constrictor agents (4,30). In humans, the few studies in which rapid intravenous saline infusion was used with the intent to render the airway wall edematous and thick have documented mild airflow obstruction (10), air trapping (7,22), and a leftward shift of the doseresponse curve to methacholine (27). No systematic changes in elastic recoil of the lung were reported (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Conversely, infusion of 10 ml/kg of saline into 10 patients with a left ventricular ejection fraction (LVEF) <40% resulted in a fall in forced expiratory volume in 1 s (FEV1), forced expiratory ratio (FER) and diffusing capacity for carbon monoxide (DLCO). 26 The same study also demonstrated lower baseline FEV1, FVC and DLCO in these subjects compared with a control group.…”
Section: Effects Of Hf On Respiratory Function Testingmentioning
confidence: 99%
“…Checking the respiratory rate in T 1 and T 2 the group corresponding to infusion of 0.5 fold BV did not presented significant change relative to the control besides that also showed a smaller difference between the times. This may be due to the increase of pulmonary blood and oxygenation improvement as another study suggests 8 . There was a significant difference only in 3 fold BV group, where all animals died, which means that all of them presented T 2 equal to zero.…”
Section: Resultsmentioning
confidence: 95%